The presence of the prophet in early modern and contemporary Islam (Handbook of Oriental studies Section 1, The Near and Middle East, 2021)
The three-volume series titled The Presence of the Prophet in Early Modern and Contemporary Islam, is the first attempt to explore the dynamics of the representation of the Prophet Muhammad in the course of Muslim history until the present.